Evaluation of Geo-Tourism Capability of Zahak Area in Hashtroud - Dr. Sayad. Asghari Saraskanroud; Dr. Fariba. Esfandyari; Dr. Vahid. Mohammadnejad; Dr. Batul. Zeinali; Saleh. Asghari Saraskanroud (جغرافیا و آمایش شهری منطقه‌ای, 2014)
In this study, the geo-tourism capability of Hashtroud Zahak area has been studied. This area has a wide range of elements and geomorphic processes for attracting  tourists interested in earth sciences. It is one of the most important historical centers of Azerbaijan from cultural and historical point of view. In this research, Hadžić model has been used. In this study, the value and importance  of each geo tourism location is estimated by three indexes, including Scientific value, secondary values and Vulnerability of that geotourism location. For this purpose, a survey was performed from 25 tourists and 6 professionals. Results indicated that geological features associated with cultural heritage have the highest score among professionals and tourists in terms of scientific value. This indicate a wide range of geological and geomorphological forms in the study area. Natural elements and cultural heritage have the highest score among professionals and tourists in terms of secondary values. Vulnerability from expert's view is 3,  that indicates  relatively high vulnerability of the area. Finally investigation of three indexes in the final assessment of the value of geo tourism indicated that , this area has a good geo tourism value.